The implementation and appraisal of a novel confirmatory HIV-1 testing algorithm in the Microbicides Development Programme 301 Trial (MDP301). - Ute Jentsch (Public Library of Science (PLoS), 2012)
Unlabelled We describe the application of a novel HIV confirmatory testing algorithm to determine the primary efficacy endpoint in a large Phase III microbicide trial. 9385 women were enrolled between 2005 and 2009. Of these women, 537 (6%) had at least one positive HIV rapid test after enrolment. This triggered the use of the algorithm which made use of archived serum and Buffy Coat samples. The overall sample set was >95% complete. 419 (78%) of the rapid test positive samples were confirmed as primary endpoints using a combination of assays for the detection of HIV-specific antibodies (EIA's and Western Blot), and for components of the virus itself (PCR for the detection of nucleic acids and EIA for p24 antigen). 63 (12%) cases were confirmed as being HIV-positive at screening or enrolment and 55 (10%) were confirmed as HIV negative. The testing algorithm confirmed the endpoint at the same visit as that of the first positive rapid test in 90% of cases and at the time of the preceding visit in 10% of cases. Of the 63 cases which were subsequently confirmed to be HIV-1 positive at or before enrolment, 54 specimens contained no detectable HIV antibodies at screening or enrolment. However, 43 were positive using an EIA which detects both HIV antigen and antibody and also had a positive p24 antigen or HIV PCR test, which was highly suggestive of acute infection. There were 6 unusual cases which had undetectable HIV-1 DNA or RNA. In 4 of the 6 cases the presence of HIV-1-specific antibodies was confirmed by Western Blot. One of these cases with an indeterminate Western Blot was a previous vaccine trial participant. The algorithm served the objectives of the study well and can be recommended for use in determining HIV as an endpoint in clinical trials. Trial registration ISRCTN.org ISRCTN 64716212.